Assessment and optimization of power networks based on a dual-loop model - Junchi Cui; Zhaoyang Guo; Shuliang Wang; Bo Song (AIP Advances)
This paper presents a novel dual-loop framework for assessing and enhancing the power network resilience during recovery and reconstruction following cascading failures. The framework combines network restoration strategies with reconfiguration to improve power network resilience. Initially, a network model and its corresponding resilience index are given, and the recovery capabilities of different repair strategies are analyzed to identify the optimal repair strategy. Subsequently, a simulated annealing algorithm is employed to reconfigure the network, enhancing its resilience. The effectiveness of the proposed framework is validated using the IEEE 118-node network as a case study. Simulation results show that the dual loop optimization model exhibits superior resilience restoration capabilities. The proposed framework can aid decision-makers in developing mitigation techniques and optimal protection strategies to ensure the resilience of the power network.